CFTR Modulator Therapy for Rare CFTR Mutants - Marco Mergiotti; Alessandra Murabito; Giulia Prono; Alessandra Ghigo (MDPI AG, 2022)
Cystic fibrosis (CF), the most common genetic disease among the Caucasian population, is caused by mutations in the gene encoding for the CF transmembrane conductance regulator (CFTR), a chloride epithelial channel whose dysfunction results in severe airway obstruction and inflammation, eventually leading to respiratory failure. The discovery of the CFTR gene in 1989 provided new insights into the basic genetic defect of CF and allowed the study of potential therapies targeting the aberrant protein. In recent years, the approval of "CFTR modulators", the first molecules designed to selectively target the underlying molecular defects caused by specific CF-causing mutations, marked the beginning of a new era in CF treatment. These drugs have been demonstrated to significantly improve lung function and ameliorate the quality of life of many patients, especially those bearing the most common CFTR mutatant F508del. However, a substantial portion of CF subjects, accounting for ~20% of the European CF population, carry rare CFTR mutations and are still not eligible for CFTR modulator therapy, partly due to our limited understanding of the molecular defects associated with these genetic alterations. Thus, the implementation of models to study the phenotype of these rare CFTR mutations and their response to currently approved drugs, as well as to compounds under research and clinical development, is of key importance. The purpose of this review is to summarize the current knowledge on the potential of CFTR modulators in rescuing the function of rare CF-causing CFTR variants, focusing on both investigational and clinically approved molecules.